Analysis of honey main sugars by size-exclusion chromatography - Sousa, Mara E.B.C. (2014)
The main constituents of honey are sugars, mainly the monosaccharides fructose and glucose (reducing sugars), which account for 80% of the total mass, while the disaccharides (especially sucrose and maltose) represent 10%. In general, fructose predominates (giving a sweeter taste to honey than sucrose), although, in some honeys, glucose (that assigns a less sweet taste than sucrose but more than maltose) may be the main sugar. The fructose/glucose mass ratio is a parameter that allows the identification of possible adulterations of honey, by signaling abnormal levels of glucose due to the addition of commercial glucose or syrups. It also allows assessing the crystallization trend of the honey, although the glucose/water ratio provides a more accurate indication of this behavior. Therefore, for marketing purposes, the quantification of glucose and fructose in honey is a key factor for establishing its quality. This work reports the validation of a method for determination of honey sugars by SEC to be used as control in the study of their determination with an electronic tongue. A set of honey samples was provided by the Portuguese National Federation of Beekeepers to obtain a national sampling which showed the natural composition variability of Portuguese honeys. The analysis were carried out with HPLC equipment from Varian and a Supelcogel C-610H column, selected because the elution does not require organic solvents. The target compounds to analyze were glucose and fructose for which well separated peaks were found in the chromatograms, which included other two, for a mix of polyssacharides and unknown substance(s). The results of a thorough validation showed that the method can be employed for quantification of these two sugars in honey samples.